Formação docente em Angola (2001-2015): currículo e política de formação de professores para o Ensino de Jovens e Adultos - Júlia Júnior, André (2017)
This research aims at investigating and analyzing teacher education in Angola (2001 - 2015), specifically the training policy of teachers of Youth and Adult Education. The methodology adopted is qualitative research of a bibliographic and documentary nature supported by sources such as the legal documents of the Republic of Angola, legislation on education, school curricula, among others. These documents aimed at analyzing and understanding the politics of teacher education. Based on the assumption that every human being has the right to quality education and education, as guaranteed by national and international standards, it is important to know how this right is carried out in the current context in Angola. Due to diverse conditionalities, this right has been deprived to many Angolans for decades. Now, after the civil war, the government, through the Ministry of Education, has reduced efforts to guarantee and expand this right through general education reforms. However, ensuring educational quality does not only require focusing attention on the technical or material aspects of education. We must also be concerned with the policy-making agents, teachers. Thus, it is understood that reforming education requires reforming the aspects that constitute the preparation of the immediate agents of pedagogical practice. In Angola, however, although teaching has been reformed, teacher education is still a great concern and challenge. The preparation of these professionals needs updating, a more adequate training, reducing authoritarianism in the teacher and difficulty of the teacher to work with participatory methods in the classroom